Left Ventricular Hypertrabeculation (LVHT) in Athletes: A Negligible Finding? - Rokas Jagminas; Rokas Šerpytis; Pranas Šerpytis; Sigita Glaveckaitė (Medicina)
Left ventricular hypertrabeculation (LVHT) used to be a rare phenotypic trait. With advances in diagnostic imaging techniques, LVHT is being recognised in an increasing number of people. The scientific data show the possibility of the overdiagnosis of this cardiomyopathy in a population of people who have very high levels of physical activity. We describe the case of a young athlete with no medical history, who presented with syncope during a marathon running race. Initial evaluation showed elevated troponin I; transthoracic echocardiography showed a trabeculated ventricle and subsequent cardiac magnetic resonance (CMR) revealed left ventricular hypertrabeculation (LVHT). During subsequent evaluation by tilt table testing, vasovagal syncope was identified as the likely aetiology of the syncope. The patient was advised to cease sports and stimulants like caffeine use. At the 29-month follow-up, CMR showed the normalisation of the non-compacted to compacted myocardial ratio and an improvement in left ventricular function, with no further syncopal episodes reported. This is an example of the physiological hypertrabeculation of the LV apex in a recreational endurance athlete, with the normalisation of the non-compacted to compacted myocardial layer ratio after detraining. Physiological hypertrabeculation, a benign component of exercise-induced cardiac remodelling, must be differentiated from non-compaction cardiomyopathy and other pathologies causing syncope. This case underscores the importance of distinguishing physiological hypertrabeculation from pathological LVHT in athletes, highlighting that exercise-induced cardiac remodelling can normalise with detraining.